The invisible life of Addie LaRue [compact disc, unabridged] - Schwab, Victoria (Macmillan Audio, 2020)
France, 1714: in a moment of desperation, a young woman makes a Faustian bargain to live forever, and is cursed to be forgotten by everyone she meets. Thus begins the extraordinary life of Addie LaRue and a dazzling adventure that will play out across centuries and continents, across history and art, as a young woman learns how far she will go to leave her mark on the world. But everything changes when, after nearly 300 years, Addie stumbles across a young man in a hidden bookstore and he remembers her name.